Knowledge and awareness towards dengue infection and its prevention: a cross sectional study from rural area of Tamil Nadu, India - Chellaiyan, Vinoth Gnana; Manoharan, Aravind; Ramachandran, Murali (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue infection transmitted by Aedes aegypti is endemic in India. Environmental changes and lack of awareness result in increase in transmission of dengue infection and rise in dengue outbreaks. The present study was conducted to determine the knowledge of dengue infection and practices towards dengue prevention among a rural population in Kancheepuram district of Tamil Nadu. Methods:The study was cross sectional study, conducted in Kadambadi village of Kanchipuram district, Tamil Nadu. The study was conducted among 224 study participants from June - August 2016. Systematic random sampling was followed for selecting the houses. A pretested, semi structured questionnaire was used. Significance of difference in proportions (qualitative variables) was calculated using Chi square test. Significance of p value was taken as p< 0.05. Results: Among the study participants, 210 (93.7%) heard about dengue infection. Fifty percent of participants responded correctly the symptoms of dengue infection. 89% responded correctly that dengue is transmitted by Aedes mosquito. Around 40% of the participants had correct knowledge about the breeding habitat and biting habit of Aedes mosquito. Study participants use various methods - mosquito coils (63.4%), mosquito nets (14.7%) for mosquito bite prevention. 24.1% does not follow any method of mosquito bite prevention. Conclusions:Though majority of the study participants heard about dengue symptoms and mosquito transmitting dengue infection, less than half were aware about breeding habits of Aedes mosquito and 25% did not follow any method of mosquito bite prevention practices. Community awareness is a key role in improvising dengue prevention practices.